Weizmannia coagulans BC99 regulates oxidative stress and serum metabolic pathways to improve allergic rhinitis: a randomized, double-blind, placebo-controlled trial - Li, Xuan; Han, Zhidong; Wu, Kaihong; Lin, Bingchai; Azeem, Saman; Jiang, Yiru; Dong, Yao; Gai, Zhonghui; Fang, Shuguang; Wu, Ying; Gu, Shaobin (Frontiers in Immunology, 2025)
BackgroundProbiotics have demonstrated potential application value in alleviating allergic diseases, but their mechanisms of action remain to be explored. This study aimed to investigate the clinical efficacy of probiotics in patients with allergic rhinitis (AR) and explore the underlying mechanisms.MethodsWe evaluated the clinical intervention efficacy of Weizmannia coagulans BC99 (BC99) in adults with AR through a randomized, double-blind, placebo-controlled trial. Seventy-eight AR patients were randomly assigned to either the BC99 gummies group (n = 40) or the placebo group (n = 38) for an 8-week intervention. Rhinitis symptom survey questionnaires, including the Total Nasal Symptom Score (TNSS), the Rhinitis Quality of Life Questionnaire (RQLQ), and the Rhinitis Control Assessment Test (RCAT), were administered and evaluated. Additionally, oxidative stress indicators, including superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA), as well as immune factors (IgA, complement C3) were measured by enzyme-linked immunosorbent assay. Serum metabolomic profiles were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS).ResultsThe results indicated that BC99 significantly alleviated nasal symptoms and improved quality of life, as evidenced by reduced TNSS and RQLQ scores (p < 0.05) and increased RCAT scores (p < 0.01). Furthermore, BC99 supplementation significantly decreased serum IgA, complement C3, EOS, and MDA levels (p < 0.05) while enhancing antioxidant capacity (increased GSH, stabilized SOD). Metabolomic analysis revealed that BC99 intervention induced 397 differential metabolite changes (136 upregulated, 261 downregulated) and significantly modulated AR-related metabolic pathways, including biosynthesis of unsaturated fatty acids, phenylalanine metabolism, and arginine biosynthesis (p < 0.05).ConclusionThis study confirms the efficacy of W. coagulans BC99 in ameliorating AR, potentially through immune modulation, oxidative stress reduction, and metabolic pathway regulation. These findings support BC99 as a promising adjunct therapy for AR, though further research is warranted to elucidate its molecular mechanisms and long-term effects.Clinical trial registrationhttps://clinicaltrials.gov, identifier NCT06680102.